Efficacy of Fungicides Against Grain Discoloration Disease of Rice - Patil, V. A.; Patel, P. B.; Ghoghari, P. D.; Kavad, N. K.; Usadadia, V. P. (International Journal of Economic Plants, 2020)
Rice (Oryza sativa L.) is one of the important cereal crop grown extensively in Gujarat. It suffers from grain discoloration fungal disease causing heavy losses at maturity stage of rice. A field experiment was laid out with the single and new combinations fungicides against rice grain discoloration disease under field conditions during kharif-2013-14, 2014-15 and 2015-16. Six fungicides at various concentrations were screened against rice grain discoloration disease. The trifloxystrobin 25% + tebuconazole 50% (0.03 %) @ 0.4 g l-1 and propiconazole 25 EC (0.025 %) @ 1.0 ml l-1 was found effective against rice grain discoloration and recorded significantly higher healthy grains.